Psikoedukasi Berbasis Komunitas untuk Memperkuat Kesiapsiagaan Psikologis dan Resiliensi pada Masyarakat Pesisir Rawan Tsunami: Kelurahan Jangkaran, Kulon Progo: Community-Based Psychoeducation to Strengthen Psychological Preparedness and Resilience in a Tsunami-Prone Coastal Community: Jangkaran Village, Kulon Progo - Rahmawan, Ridwan; Setyaningtyas, Angelina Dyah Arum; Putrikita, Katrim Alifa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Coastal communities in Jangkaran Village face both physical and psychological disaster-related vulnerabilities, including damaged coastal vegetation, inadequate evacuation routes, limited shelters, low knowledge, limited emotional readiness, and insufficient self-efficacy in responding to emergencies. This community engagement program aimed to enhance psychological preparedness through psychoeducation and to empower local cadres to disseminate disaster mitigation information sustainably. The activities involved initial assessments through observation, focus group discussions, and interviews, followed by psychoeducational sessions on emotion regulation, risk understanding, and mental simulation of evacuation procedures, which were evaluated through pre- and post-intervention measurements. The results indicated improvements in community understanding, emotional regulation, and confidence in decision-making during emergencies. This program concludes that psychoeducation combined with cadre involvement is an effective strategy for strengthening psychological preparedness in coastal communities and recommends its implementation in other disaster-prone areas.